KUALITAS INFORMASI DARI SISTEM INFORMASI POSYANDU (SIP) BERBASIS KOMPUTER UNTUK MENDUKUNG SURVEILANS KESEHATAN IBU & ANAK OLEH MASYARAKAT PADA DESA SIAGA - Khoiri, Abu (FKM - UNEJ, 2010)
One of the Alert Village activities is implementation of surveillance based on community namely surveillance of maternal and child health through activities which are conducted at the Integrated Health Services Post.Â Surveillance activities are conducted by a cadre who records and reports using information system of the integrated health services. The resulted information is weight,Â childâs nutritional status, immunization, risk level of pregnant women, immunization of Tetanus Toxoid, list of mothers and children who are either life or lifeless, and presence of health workers during providing services. Based on the previous study, resulted information was difficult to reaccess and had not resulted the complete, accurate, and clear information. The objective of this research was to develop information system of the integrated health services post for supporting surveillance of maternal and child health based on community at the alert village. Design of this research was pre-experimental (one group pretest-posttest). Subject consisted of the end user Â (cadres of the integrated health services post). Data were analyzed using considered average of resulted information between before and after developing the information system.The score of the considered average on the new system (3.07) was higher than the score of the considered average on the old system (2.54). It means that the new system could overcome problems related with quality of information namely accessibility, completeness, accurateness, and clarity. KeywordsÂ Â Â Â Â Â Â Â Â : Information System, Integrated Health Services Post, Information Quality